1990
DOI: 10.1002/ajim.4700170106
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of health effects of grain dust exposures

Abstract: Grain dust has a long history of association with disease, and its effects on various organs have been reported for many years. Inflammatory diseases of the eyes, nose, and skin may be caused by both direct irritation and immune-based reactions. The lung and airways frequently suffer adverse effects. Asthma is well documented as being a result of exposure. Several studies show increased incidences of respiratory symptoms and of reduced pulmonary function in grain workers. Grain dust should be regarded as a dus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 16 publications
0
21
0
Order By: Relevance
“…The physical and chemical compositions of organic dusts vary and are affected by the dust source, geographic region, temperature, humidity, and other factors. Grain dust constituents include fractured grain kernels, trichome particles, insects or insect parts, silica, bacteria and molds, and chemical residues (7).…”
Section: Organic Dust Toxic Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…The physical and chemical compositions of organic dusts vary and are affected by the dust source, geographic region, temperature, humidity, and other factors. Grain dust constituents include fractured grain kernels, trichome particles, insects or insect parts, silica, bacteria and molds, and chemical residues (7).…”
Section: Organic Dust Toxic Syndromementioning
confidence: 99%
“…A specific dose -exposure relationship is usually not possible to determine, however. Measurements up to 1,000 mg/m (3) of organic dust have been reported in work areas with a usual range of 5 to 50 mg/m (3) , 10% being respirable (7). Exposure to greater than 90 to 100 mg/m (3) of respirable grain dust for 1 to 2 hours provoked ODTS in two of six subjects (23).…”
Section: Dose-responsementioning
confidence: 99%
“…Several reports have suggested that unprotected dust exposures in agricultural settings may lead to pulmonary fibrosis [5][6][7]. Grain dust has a long history of association with disease, and its adverse effects on various organs such as eyes, nose, skin, lung and airways have been described [8].…”
Section: Introductionmentioning
confidence: 99%
“…Ambient aerosols, or particulate air pollution, in the inhalable size range have been shown through various epidemiologic studies to have clear associations with increased respiratory and cardiovascular disease resulting in increased morbidity and mortality (Dockery et al, 1993;Dockery et al, 1992;Ozkaynak & Thurston, 1987;Pope et al, 1991;Dockery et al, 1989;Bates & Sizto, 1983;Pope, 1989;Katsouyanni et al, 1997;Samet et al, 2000;. Other aerosols such as organic dusts also have been linked to adverse health effects (Malmberg, 1990;Hurst & Dosman, 1990;Chan-Yeung et al, 1992;Enarson & Chan-Yeung, 1990;Weber et al, 1993;Larsson et al, 1994;Donham, 1990;Rylander, 1990;Schenker, 2000;Heederik et al 2007;Castranova et al, 1996). It has been suggested 142 E. J. SCOTT DUNCAN ET AL. that particles in the size range <2.5 µm may have the most significant effect on respiratory health (Schwartz et al, 1996;Schwartz & Neas, 2000).…”
Section: Introductionmentioning
confidence: 99%